Electrochemical degradation of dye on TiO2 nanotube array constructed anode. (November 2019) - Gui, Lin; Peng, Jianghua; Li, Peng; Peng, Ruichao; Yu, Ping; Luo, Yunbai
Abstract: A high oxygen evolution potential (2.6V) and conductivity of Ti/TiO2 NTs/Ta2 O5 -PbO2 anode was fabricated by mixed metal oxide. A well-aligned TiO2 nanotubes was successfully prepared by using 1-butyl-3-methylimidazolium tetrafluoroborate as the electrolyte. The surface structure of anodes were characterized by scanning electron microscope, X-ray diffraction and energy dispersive X-ray spectroscopy. During the electrochemical degradation experiments, the effects of different anodes, current density, initial pH value and concentration were discussed. The results showed that co-doped Ta2 O5 coating is an effective method to improve the surface morphology and the electrochemical characterization of Ti/TiO2 NTs/PbO2 . At the initial pH value of 3 and current density of 12 mA cm −2, the removal rates of Acid Orange 7 and total organic carbon with Ti/TiO2 NTs/Ta2 O5 -PbO2 anode were almost 100% and 98.3%. Comparing with Ti/PbO2 anode at the same charge consumption (3 A h L −1 ), the instantaneous current efficiency of the Ti/TiO2 NTs/Ta2 O5 -PbO2 anode and Ti/TiO2 NTs/PbO2 anode increased by 40.0% and 27.1%, respectively. The highest rate of k .OH on Ti/TiO2 NTs/Ta2 O5 -PbO2 anode was 12.4 μmol (L min) −1 . The organic dyes are oxidized into CO2 and H2 O by . OH radical. The reaction process and mechanism during the electrochemical degradation were discussed. Graphical abstract: Image 1 Highlights: High oxygen evolution potential and conductivity of Ti/TiO2 NTs/Ta2O5-PbO2 anode. A well-aligned TiO2nanotubes were prepared by using ionic liquids. Co-doped Ta2O5can improve the surface morphology and electrochemical characterization. The removal rates of AO 7 and TOC with Ti/TiO2 NTs/Ta2O5-PbO2anode were 100% and 98.3%. The electrochemical degradation process and mechanism of dye are proposed.